Analysis of the Effect of Price and Product Reviews on Online Purchase Decisions Through Shopee in the Midst of the Covid-19 Pandemic (A Case Study: Shopee Consumers in Banjarnegara Regency, Central Java) - Aisyah Aisyah; Atiyah Fitri; Fahmi Syahbudin (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2021)
This study aims to determine the effect of price and product reviews on online purchasing decisions through Shopee during the Covid-19 pandemic in Banjarnegara Regency, Central Java. This study uses a quantitative approach. The data collection technique was conducted with a questionnaire. The number of samples in this study was 120 respondents using the purposive sampling method or with certain criteria, namely, the respondents are Shopee consumers who live in Banjarnegara Regency, Central Java, and have experience doing online transactions at Shopee at least 2 times since the outbreak of the Covid-19 pandemic in Indonesia. The data analysis technique used validity test, reliability test, multiple linear regression analysis and t-test (partial), and F test (simultaneous), and the coefficient of determination (R2). The data processing uses SPSS version 26.0. The results of this study indicate that prices and product reviews partially and simultaneously influence online purchasing decisions through Shopee during the Covid-19 pandemic in Banjarnegara Regency, Central Java.